The Snowball Throwing Learning Model on Economic Learning Outcomes as Material of Demand and Supply Class X at MA Islamiyah Padang Garugur North Padang Lawas - Rambe, Saima; Harahap, Fitriani; Siregar, Hendra Mahmud (Yayasan Perguruan Kampus, 2024)
This research aims 1) To find out an overview of the implementation of the snowball throwing model. 2) To find out the picture of economics students' learning outcomes on the main topic of demand and supply before and after using the snowball throwing model. 3) To see the influence of the application of the snowball throwing model on the learning outcomes of economics students on the main topic of supply and demand in Class X MA Islamiyah Padang Garugur. The population in this study were all students of Class X MA Islamiyah Padang Garugur, consisting of 1 class totaling 38 students. The sample IS Class X with a total of 38 people. Based on the results of the research conducted, it can be concluded that the description of the use of the snowball throwing model in Class An overview of the results of studying economics on the main topic of demand and supply in Class Meanwhile, the description of the results of studying economics on the main topic of demand and supply in Class Through the hypothesis test carried out, it is known that the calculated t value is 2.810, while the significant value obtained is 0.000, so it is known that the Sig. (2-tailed) < 0.05.